PENGGUNAAN MODEL REALISTIC MATHEMATICS EDUCATION DALAM MENINGKATKAN KEMAMPUAN NUMERASI PADA SISWA KELAS V SD 1 PEGANJARAN - Nailul Muna; Diana Ermawati; Lintang Kironoratri (Jurnal Pendidikan Dasar Flobamorata, 2023)
This study aims to find out that learning using the Realistic Mathematics Education model can improve the numeracy skills of fifth grade students at SD 1 Peganjaran. Students have low numeracy skills in learning mathematics. This can be seen from the pre-cycle results using knowing and applying numeracy cognitive levels with 6 students who complete with a percentage of 31.58% and students who do not complete as many as 13 students with a percentage of 68.42%. This research includes classroom action research conducted at SD 1 Peganjaran. The subject consisted of 19 students, including 12 male students and 7 female students. Data collection techniques using test techniques, observation, interviews and documentation. Analysis of the data used using quantitative and qualitative data. Based on the results of the research, the results of the evaluation test in cycle I completed 13 students with a percentage of 68.42% (medium numeracy ability) and experienced an increase in cycle II with 19 students who completed 100% (high numeracy ability). The results of this study can be concluded that the Realistic Mathematics Education model can improve students' numeracy skills.